Comparison of platelet to lymphocyte ratio and neutrophil to lymphocyte ratio in women with preterm premature rupture of membranes and women with preterm delivery - Khodadost, Mahsa; Ghavami, Zahra; Dargahi, Rogayeh; Amani, Firouz (International Journal Of Community Medicine And Public Health, 2024)
Background: Considering the adverse effect of PROM on birth outcomes and the condition of mother and fetus, early identification of risk factors of PROM and their control can reduce the occurrence of adverse outcomes for mother and fetus and improve their health. This study was conducted with the aim of comparing PLR and NLR in women with PROM and women with preterm delivery. Methods: This case-control study was conducted on 155 women with PPROM as case group and 155 women with preterm delivery as control group. Age, gestational age, type of delivery, baby's birth weight, gravida, parity, APGAR score, rate of hospitalization in Neonatal Intensive Care Unit (NICU), occurrence of neonatal sepsis and development of respiratory distress syndrome (RDS) were recorded from women's medical records. Also, the results of blood tests and PLR and NLR values were calculated for each pregnant woman. Collected data were analyzed by statistical methods in SPSS version 24. Results: The average gestational age and weight of babies at birth time in the case group were significantly lower than those with preterm delivery. The mean of NLR in case group with 4.8±2.5 was significantly higher than control group with 4.2±2.2. The mean of PLR in case group with 111.5±47.6 was significantly higher than control group with 100.98±43.4. Conclusions: The high values of PLR and NLR in the women with PROM compared to women with preterm delivery can be a marker to identify the risk of PPROM in pregnant women.